The Design and Location Characteristics of Wildlife Overpasses in Hungary - Tari, Tamás; Takács, Attila (JOURNAL OF LANDSCAPE ECOLOGY, 2023)
Hungary's motorway network has developed significantly over the past twenty years. These developments have increased the length of fenced roads, which also means increased habitat fragmentation effects. Wildlife crossings have been built on new sections to reduce isolation caused by roads. This study examined 57 wildlife overpasses using satellite imagery. We determined the internal and overall widths of the crossings, their total length and the length of the noise barriers, as well as the width-to-length ratio. The crossings were classified according to ramp design, noise barrier material and noise barrier run-down. In addition, a surface cover map was used to examine landscape features within 500 m of the crossings and evaluate the crossings' placement. Our results show that the average width of the overpass corridor was 14.4 m. The width-to-length ratio was 0.16. Based on this, we concluded that the wildlife crossings in Hungary could be classified as narrow crossings. There was also considerable variation in design characteristics, with the crossings studied not being uniform in either ramp design or noise barrier characteristics. The results of the placement's landscape characterisation indicate that many overpasses in agricultural areas are particularly favourable for roe deer (Capreolus capreolus).
Keywords: habitat fragmentation; large ungulates; noise screening; traffic; isolation effect